Report of an equine forelimb varus case - DIAKAKIS (Ν.ΔΙΑΚΑΚΗΣ) N.; DESIRIS (Α. ΔΕΣΙΡΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Angular limb deformities could be congenital oracquired and could result from: a) asymmetrical growth from the distal radial epiphysis, b) incomplete growth of the carpal bones, the second and fourth metacarpal bones and c) laxity of the carpal joints. The causes of these conditions are numerous. As far as congenital angular deformities are concerned, the cause may be due to intrauterine malposition, overnutrition of the mare in the latter half of pregnancy, joint laxity, twin pregnancy, short gestation period, defective endochondral ossification of the carpal bones or maldevelopment of the second and fourth metacarpal bones. Specifically for the defective endochondral ossification of the carpal bones, the condition is put down to placentitis or reduced uterine blood supply, which prohibits the development of the placenta. Moreover, others claim that toxic and hormonal factors pray a role in the aetiopathogenesis of the disease. As far as the acquired angular limb deformity is concerned, it can be due to growth plate injury, deterioration of an existing subtle congenital deformity, excessive contralateral limb weight bearing, over nutrition, improper trimming, excessive exercise or bad training and poor limb conformation. This report describes the case of a 15-month-old foal, which was admitted to the Veterinary Teaching Hospital, Faculty of Veterinary Medicine, A.U.Th. with bilateral forelimb varus, which was due to overfeeding of the animal. Based on the radiological findings and the age of the animal, the transection of the periosteum (periosteal stripping) from the concave side was the recommended treatment of choice. On re-examination, 4months post-operatively, carpal varus had resolved completely in both forelimbs.